Pseudo-trisomy 13 in a fetus: further support for autosomal recessive inheritance - Ütine, G. Eda; Alanay, Yasemin; Aktaş, Dilek; Talim, Beril; Kale, Gülsev; Tunçbilek, Ergül (The Turkish Journal of Pediatrics, 2008)
Pseudo-trisomy 13 is defined in chromosomally normal patients with holoprosencephaly and associating features suggestive of trisomy 13. An autosomal recessive pattern of inheritance for this situation is most likely, but a gene for this condition has not yet been mapped. A fetus is presented with phenotypic features reminiscent of trisomy 13 but a normal karyotype, 46, XY. The pregnancy was terminated due to severe fetal malformations. In autopsy, the fetus had semilobar holoprosencephaly, hydrocephaly and dysmorphic features such as hypotelorism, cleft lip, a flat nose with a single nostril, low-set ears, postaxial polydactyly in all extremities, left unilateral pes equinovarus and pulmonary segmentation defect on the right. The parents were 2nd cousins once removed. Holoprosencephaly and polydactyly with or without other findings in chromosomally normal patients should raise the suspicion of pseudo-trisomy 13 syndrome, particularly when parental consanguinity is present.